CIPP Evaluation on the Literacy Program in Improving Reading Proficiency in Senior High School - Marni Hartati; Dedy Achmad Kurniady; Udin Syaefudin Sa’ud; Diding Nurdin (AL-ISHLAH: Jurnal Pendidikan, 2025)
Reading proficiency is a critical component of student success in senior high school and requires structured, ongoing evaluation. This study evaluates the effectiveness of a high school literacy program in enhancing reading proficiency using the CIPP (Context, Input, Process, Product) evaluation model. A concurrent embedded mixed-methods approach was employed, with quantitative data as the primary source and qualitative data as complementary. The study involved 57 teachers through surveys, supported by interviews, observations, and document analysis. Data were analyzed descriptively and triangulated using source and method validation. The findings indicate strong alignment of the literacy program with national education policies and the Independent Curriculum. Context and input aspects were rated highly, particularly in curriculum design and policy support. However, gaps remain in teacher competence, availability of literacy facilities, and student motivation. The process evaluation revealed well-structured planning, yet highlighted the need for improved student engagement and more effective learning strategies that foster critical thinking. Product evaluation showed progress in reading comprehension, text analysis, and skill application, though students’ academic vocabulary and communication skills remain underdeveloped. While the literacy program demonstrates positive outcomes, its effectiveness can be enhanced by addressing teacher training, expanding facility access, and incorporating interactive, problem-based learning. The study recommends multiliteracy-focused professional development and suggests future longitudinal research to assess the sustainability and broader impact of literacy interventions across diverse school contexts.